Difference between male and female ice hockey players in muscle activity, timing, and head kinematics during sudden head perturbations - Debison-Larabie, C.; Murphy, B. A.; Holmes, M. W. R. (Journal of Applied Biomechanics, 2018)
This study examined sex differences in head kinematics and neck muscle activity during sudden head perturbations. Sixteen competitive ice hockey players participated. Three muscles were monitored bilaterally using surface electromyography: sternocleidomastoid, scalene, and splenius capitis. Head and thorax kinematics were measured. Head perturbations were induced by the release of a 1.5-kg weight attached to a wire wrapped around an adjustable pulley secured to the participant`s head. Perturbations were delivered in 4 directions (flexion, extension, right lateral bend, and left lateral bend). Muscle onset times, muscle activity, and head kinematics were examined during 3 time periods (2 preperturbation and 1 postperturbation). Females had significantly greater head acceleration during left lateral bend (31.4%, P < .05) and flexion (37.9%, P = .01). Females had faster muscle onset times during flexion (females = 51 ± 11 ms; males = 61 ± 10 ms; P = .001) and slower onset times during left lateral bend and extension. Females had greater left/right sternocleidomastoid and scalene activity during extension (P = .01), with no difference in head acceleration. No consistent neuromuscular strategy could explain all directional sex differences. Females had greater muscle activity postperturbation during extension, suggesting a neuromuscular response to counter sudden acceleration, possibly explaining the lack of head acceleration differences.